Development and functionalization of subwavelength grating metamaterials in silicon-based photonic integrated circuits - Naraine, Cameron Mitchell (My University, 2024)
Silicon photonics (SiP) has become a cornerstone technology of the modern age by leveraging the mature fabrication processes and infrastructure of the microelectronics industry for the cost-effective and high-volume production of compact and power-efficient photonic integrated circuits (PICs). The impact that silicon (Si)-based PICs have had on data communications, particularly data center interconnection and optical transceiver technologies, has encouraged SiP chip development and their use in other applications such as artificial intelligence, biomedical sensing and engineering, displays for augmented/virtual reality, free-space communications, light detection and ranging, medical diagnostics, optical spectroscopy, and quantum computing and optics. To expand the functionality and improve the performance of SiP circuits for these surging applications, subwavelength grating (SWG) metamaterials have been thoroughly investigated and implemented in various passive integrated photonic components fabricated on the silicon-on-insulator (SOI) platform. SWG metamaterials are periodic structures composed of two materials with different permittivities that exhibit unnatural properties by using a period shorter than the guided wavelength of light propagating through them. The ability to synthesize the constituent SiP materials without any need to alter standard fabrication procedures enables precise, flexible control over the electromagnetic field and sophisticated selectively over anisotropy, dispersion, polarization, and the mode effective index in these metastructures. This provides significant benefits to SOI devices, such as low loss mode conversion and propagation, greater coupling efficiencies and alignment tolerances for fiber-chip interfaces, ultrabroadband operation in on-chip couplers, and improved sensitivities and limits of detection in integrated photonic sensors. Parallel to the rise of SiP technology is the development of other materials compatible with mature PIC fabrication methods both in the foundry (e.g., silicon nitride (Si3N4)) and outside the foundry (e.g., high-index oxide glasses such as aluminum oxide (Al2O3) and tellurium oxide (TeO2)). Si3N4 offsets the pitfalls of Si as a passive waveguiding material, providing lower scattering and polarization-dependent losses, optical transparency throughout the visible spectrum, increased tolerance to fabrication error, and better handling of high-power optical signals. Meanwhile, Al2O3 and TeO2 both serve as excellent host materials for rare-earth ions, and TeO2 possesses strong nonlinear optical properties. Using a single-step post-fabrication thin film deposition process, these materials can be monolithically integrated onto Si PICs at a wafer scale, enabling the realization of complementary-metal-oxide-semiconductor (CMOS)-compatible, hybrid SiP devices for linear, nonlinear, and active functionalities in integrated optics. While SWG metamaterials have widely impacted the design space and applicability of integrated photonic devices in SOI, they have not yet made their mark in other material systems outside of Si. Furthermore, demonstrations of their capabilities in active processes, including optical amplification, are still missing. In this thesis, we present a process for developing various SWG metamaterial-engineered integrated photonic devices in different material systems both within and beyond SOI. The demonstrations in this thesis emphasize the benefits of SWG metamaterials in these devices and realize their potential for enhancing functionality in applications such as sensing and optical amplification. The objective of the thesis is to highlight the prospects of SWG metamaterial implementation in different media used in integrated optics. This is accomplished by experimentally demonstrating SWG metamaterial waveguides, ring resonators and other components composed of different hybrid core-cladding material systems, including Si-TeO2 and Si3N4-Al2O3. Chapter 1 introduces the background and motivation for integrated optics and SWG metamaterials and provides an overview and comparison of the different materials explored in this work. Chapter 2 presents an initial experimental demonstration of TeO2-coated SOI SWG metamaterial waveguides and mode converters. It also details the design of fishbone-style SWG waveguides aimed at lowering loss and enhancing mode overlap with the active TeO2 cladding material in the hybrid SiP platform. Chapter 3 details an open-access Canadian foundry process for rapid prototyping of Si3N4 PICs, emphasizing the Si3N4 material and waveguide fabrication methods, as well as the design and characterization of various integrated photonic components included in a process design kit. The platform is compared against other Si3N4 foundries, and plans for further development are also discussed. Chapter 4 reports the first demonstration of SWG metamaterial waveguides and ring resonators fabricated using a Si3N4 foundry platform. The measured devices have a propagation loss of ∼1.5 dB/cm, an internal quality factor of 2.11·10^5, and a bulk sensitivity of ∼285 nm/RIU in the C-band, showcasing competitive metrics with conventional Si3N4 waveguides and SWG ring resonators and sensors reported in SOI. Chapter 5 presents work towards an SWG metamaterial-engineered waveguide amplifier. The fabricated device, based in Si3N4 and functionalized by an atomic layer deposited, erbium-doped Al2O3 thin film cladding, exhibited a signal enhancement of ∼8.6 dB, highlighting its potential for on-chip optical amplification. Methods to reduce the loss within the material system are proposed to achieve net gain in future devices. Chapter 6 summarizes the thesis and discusses pathways for optimizing the current devices as well as avenues for exploring new and intriguing materials and devices for future applications in integrated photonics.
Development and functionalization of SWG metamaterials in Si-based PICs
Keywords: photonics; integrated photonics; silicon photonics; integrated optics; subwavelength grating; metamaterial; silicon; silicon nitride; aluminum oxide; tellurium oxide; rare earth; erbium; ring resonator; waveguide amplifier; optical amplifier; optical waveguide